(untitled) (Ad Americam, 2013)
The aim of this article is to discuss the role of such organizations as the Family Research Council and Focus on the Family, which together constitute what is sometimes called Dr. James Dobson’s “family values empire.” Both of these organizations are an important part of the American Religious Right movement. While the Family Research Council has been extremely important in terms of political involvement, it would probably not have been able to gain its strength without cooperation with Focus on the Family, which in many cases served as a tool in its grassroots networking. Therefore, this paper includes an analysis of both organizations’ agendas.